The associations between thyroid-related hormones and the risk of thyroid cancer: An overall and dose-response meta-analysis - Wang, Zheng; Lin, Yuxin; Jiang, Yixian; Fu, Rong; Wang, Yabing; Zhang, Qian (Frontiers in Endocrinology, 2022)
Objective: Thyroid cancer (TC) is one of the most common malignant tumours of the endocrine system. Thyroid-stimulating hormone (TSH) is known as being a risk factor for TC, but other thyroid-related hormones are inconsistently associated with TC. The purpose of this study was to comprehensively evaluate the relationships between thyroid-related hormones and the risk of TC. Methods: This study utilized searches of PubMed, Embase, Web of Science and Cochrane library up to the date of March 31st, 2022. Additionally, we performed a systematic review of related original studies combining overall and dose–response meta-analyses. Results: A total of 30, 5 and 7 articles were included in the meta-analyses of TSH, Free triiodothyronine (FT3), free thyroxine (FT4) and TC risk with 58437, 6813 and 7118 participants respectively. An increased risk of TC was associated with high TSH exposure (OR=1.28, 95% CI: 1.19-1.37, P<0.001) in the overall meta-analysis. For every 1 mU/L increase in TSH, the risk of TC increased by 16%. However, in those studies that used healthy subjects as controls, the association was not statistically significant(P=0.62). Additionally, high serum FT3 demonstrated a reduced risk of TC, with a combined OR of 0.86 in the fixed-effect model (95% CI: 0.81–0.90, P<0.001). In addition, a statistically significant increase in TC risk was found when FT4 concentrations reached a certain threshold (approximately 2.2 ng/dL) in the dose-response meta-analysis. Conclusions: Significant associations between thyroid-related hormones and the risk of TC were found in this study. Further research is needed to understand the underlying mechanisms.